As práxis de inclusão escolar em uma escola municipal de Uberlândia (2005 – 2019) - Silva, Eliete Antonia da (2022)
This research revolves around special education in Brazil, with a particular focus on the municipality of Uberlândia, MG, during the period from 2005 to 2019. The objective is to examine the educational and social inclusion of students with disabilities in regular 1st to 5th-grade classrooms, with a specific emphasis on a municipal school located in the southern zone on the outskirts of the city. The research question aims to understand how this school has promoted the educational and social inclusion of students with disabilities. The central question raised is whether the pedagogical practices in regular classrooms promote inclusion or reproduce inequality and social exclusion. The main goal is to describe and analyze how the education institution has promoted the education and social inclusion of students with disabilities, seeking to understand the relationships within this process using the interpretative paradigm of inclusion, with a focus on the convergence between theory and practice. The methodology employed was a qualitative approach with a historical, descriptive, and content analytical character, utilizing documents, speeches and interviews. Critical analysis was conducted on various sources, including official documents (laws, decrees, resolutions, opinions, regulations, and minutes), semi-structured interviews, questionnaires, and specific and extensive bibliographies related to the topic. The analyses were guided by Bordieu’s concepts such as “excluded from within”, “legitimate culture”, “culture capital”, “rational pedagogy”, and others. The interviews made use of oral history methodologies and techniques, involving eighteen teachers and two analysts. Observation reports were generated during the research period, which were used for analysis and interpretation of the accounts. The research revealed the challenges and limitations faced by the interviewed teachers, including difficulties in relationships between regular classroom teachers and those involved in Specialized Educational Assistance (AEE), the absence of or limited specialized training, limited family participation and collaboration, and overcrowded classrooms. Although the school has had special education as a mode of instruction since its inception in 1994, individual efforts have driven moments of inclusivity with some successful outcomes. In general, social integration still occurs in regular classrooms. Both educational and social inclusion are irreversible paths, and both perspectives, learning and socialization, should go hand in hand while respecting each student’s limitations. It is important to note that the fundamental social function of educational institutions is to facilitate the teaching and learning of all their students.